Gender : a Caribbean multi-disciplinary perspective - Leo-Rhynie, Elsa ed. (Ian Randle Pub. KingstonJM, 1997)
Provides a comprehensive study of gender issues as they relate to the Caribbean region. Addresses gender issues on law; education; language, poetry and prose; health; and, agriculture.